Are We Islamic Young Scholars? Profiling Excellent Students at Madrasah - Toyyibah Toyyibah; Dewi Nur Suci (Institut Agama Islam Negeri Imam Bonjol Padang, 2019)
Madrasah as one of educational institutions under Ministry of Religious Affairs in Indonesia has been rapidly enhanced to construct civilized generations that can contribute to the Muslim transmission. One of which is through the concern on developing student’s academic tenacity in some learning subjects of astronomy, physics, chemistry and biology in madrasah. Regarding to this growth, this article is intended to elaborate the inspiring students’ profiles at secondary madrasah of Insan Cendekia Serpong (ICS) for their grit, independence and perseverance in education that they excel astronomy, physics, chemistry and biology. By interviewing the students, teachers, parents and peers, and documenting the management of institution, this research elucidates that the socio-cultural factors and the students’ beliefs in nature can optimize the students’ intrinsic and extrinsic motivations for the advancement of their academic tenacity in natural science subjects. Accordingly, the exemplary students of madrasah can be the agent of change maintaining tradition of being knowledge pioneer that instill a self-concept of being a scientific and religious scholar. Madrasah is also an appropriate institution to integrate and deepen student’s spirituality and modern knowledge.